Influence of indole acetic acid, arginine and mango fruit waste biochar on nutrients, chlorophyll contents and antioxidants of Fenugreek in salt affected soil - Misbah Hareem; Sammina Mahmood; Subhan Danish; Rana Khalid Iqbal; Abdullah A. Alarfaj; Sulaiman Ali Alharbi (Scientific Reports)
Abstract Salinity stress disrupts water uptake and nutrient absorption, causing reduced photosynthesis, stunted growth, and decreased crop yields in plants. The use of indole acetic acid (IAA), arginine (AN), and mango fruit waste biochar (MFWB) can be effective methods to overcome this problem. Indole acetic acid (IAA) is a natural auxin hormone that aids cell elongation and division, thereby increasing plant height and branching. L-arginine, an amino acid, is crucial for plant defense mechanisms, forming proline, polyamines, and nitric oxide, which regulate biological activities and prevent oxidative damage. Mango fruit waste biochar enhances soil fertility and water retention, thereby enhancing fruit development and yield. This study investigates the effects of combining IAA and AN as amendments to fenugreek, with and without MFWB. Four treatments (control, 2mM IAA, 250 mg/L AN, and 250 mg/L AN + 2mM IAA) study were conducted in four replications using a completely randomized design. Results demonstrate that the 250 mg/L AN + 2mM IAA with MFWB treatment led to a significant rise in fenugreek plant length (30.26%), plant fresh weight (36.37%), and plant dry weight (15.78%) over the control under salinity stress. There was a notable increase in chlorophyll a (5.13%), chlorophyll b (14.06%), total chlorophyll (7.79%), and shoot N, P, K from the control under salinity stress also showing the potential of 250 mg/L AN + 2mM IAA with MFWB. In conclusion, applying 250 mg/L AN + 2mM IAA with MFWB is a strategy for alleviating salinity stress in fenugreeks.